Islands in time : island sociogeography and Mediterranean prehistory (Routledge, 1996)
1. Islands in time : an introduction -- 2. Approaches to island archaeology -- 3. The colonisation of the Mediterranean islands -- 4. Insularity and human ecology -- 5. Elaboration and continuity in Mediterranean island prehistory -- 6. Networks of interaction in Mediterranean island prehistory -- 7. Island sociogeography and Mediterranean prehistory.